Brand Crisis Management in the context of Firestorm Online social media - Tomasz DRYL (Communications of International Proceedings, 2021)
One of the hallmarks of modern times is the prevalence of internet communication, especially communication on social media. It can take the form of positive social messages, but also negative ones, especially dangerous for the participants of the communication process. Negative social messages are very interesting from the point of view of communication science and management science. They are the subject of scientific considerations in this article. The purpose of the article is to attempt to define the brand crisis caused by negative eWOM whisper marketing messages, to define and characterize the phenomenon of Firestorm on line social media, to refer to brand crisis management in social media, and to indicate potentially useful activities of organizations responding to the brand crisis caused by Firestorm on line. Detecting, preventing and mitigating the effects of viral negative eWOM messages in online brand communities are, according to many scientists and management practitioners, a critical managerial priority. The vast majority of organizations (72%) assess their readiness on Firestorm on line as less than average, which proves the need to study the phenomenon and develop appropriate management tools. Undoubtedly, this is one of the most important tasks facing the organization's managers for the coming years.
Keywords: Crisis management; electronic word-of-mouth marketing eWOM; brand crisis; Firestorm on line